Deep Extraction - Mills, DiAnn (Carol Stream, Illinois : Tyndale House Publishers, Inc., 2017)
"A pacemaker should have saved oil and gas magnate Nathan Moore's life. Instead, it provided his killer with a seemingly perfect means of execution. A bombing at one of Nathan's oil rigs days earlier indicates his death could be part of a bigger conspiracy, a web Special Agent Tori Templeton must untangle. But her first order of business is separating the personal from the professional--the victim's wife, her best friend, is one of the FBI's prime suspects"--Amazon.com.
Keywords: United States -- Federal Bureau of Investigation -- Fiction -- Officials and employees; Petroleum industry and trade -- Fiction; Oil well drilling rigs -- Fiction; Bombings -- Fiction; Murder -- Fiction -- Investigation; Best friends -- Fiction; Christian fiction; Thrillers (Fiction)